PENELITIAN KEPUSTAKAAN - nursapia nursapia (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2014)
One of the research literature (library research) retrieval of data or materials needed to complete the study came from the library, including books, ensklopedi, dictionaries, journals, documents, magazines and so on. Criteria used to select reading materials that (a) recency (recency) and (b) relevance (relevance). Except for historical research, should avoid the use of reading materials that are already old and more recent selected sources. Source that has long been possible to load the theories or concepts that are no longer valid, because kebenarnnya theory has been refuted by newer or more recent research results.